Determination Analysis of Indonesian Palm Oil Commodities in the Covid-19 Pandemic Era on Indonesian Per Capita Gdp and Export Tax Revenues - Ernesth Cancerio Reynaldo; Wahyu Murti (PT. Publikasiku Academic Solution, 2023)
Background: The fundamental problem faced in the process of economictransformation in Indonesia is that the GDP growth of the agricultural andplantation sectors is still relatively low and the contribution of tax revenuefrom exports has not been optimal, especially in the midst of the Covid-19pandemic era.Aim: The data is compiled in the form of panel data consisting of 10provinces producing the largest production of palm oil in Indonesia and witha time series of research period 2012-2021. The research model wasformulated as a linear model and analyzed recursively using linearregression using the ordinary least squares method (OLS).Method: This study uses the explanatory method to explain the causalrelationship in Indonesia's GDP growth model per capita and Indonesia'sexport tax revenue through hypothesis testing.Findings: The research findings are that production, selling prices,exchange rates, and exports have a simultaneous effect on Indonesia's GDPper capita and export tax revenues. In part, Indonesia's GDP per capita ismore determined by production, selling prices, and exchange rates.Meanwhile, some export tax revenues are more influenced by production andselling prices